2017
DOI: 10.1155/2017/4079793
|View full text |Cite
|
Sign up to set email alerts
|

Image Encryption Algorithm Based on Hyperchaotic Maps and Nucleotide Sequences Database

Abstract: Image encryption technology is one of the main means to ensure the safety of image information. Using the characteristics of chaos, such as randomness, regularity, ergodicity, and initial value sensitiveness, combined with the unique space conformation of DNA molecules and their unique information storage and processing ability, an efficient method for image encryption based on the chaos theory and a DNA sequence database is proposed. In this paper, digital image encryption employs a process of transforming th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Along with this analysis, the proposed scheme was compared to two representative methods from other schemes [34,35,49,50]; Table 5 presents the correlation coefficient results for the encrypted Lena image. e proposed scheme obtained results superior to those of the reference methods, as the encrypted image correlation coefficient values were smaller than those obtained by the reference methods.…”
Section: Correlation Coefficient Analysismentioning
confidence: 99%
“…Along with this analysis, the proposed scheme was compared to two representative methods from other schemes [34,35,49,50]; Table 5 presents the correlation coefficient results for the encrypted Lena image. e proposed scheme obtained results superior to those of the reference methods, as the encrypted image correlation coefficient values were smaller than those obtained by the reference methods.…”
Section: Correlation Coefficient Analysismentioning
confidence: 99%
“…Meanwhile, researchers have found that exclusive features of DNA computing like enormous parallelism, immense information storage and revolutionary low power consumption have a great potential in enhancing the security of the cryptosystems. Several image cryptosystems have been proposed by different authors in recent past by synthesizing the metrics of DNA technology and hyperchaotic system [27,28]. Although, these systems enhances the security but the practical implementation becomes very difficult [29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, image encryption is an extremely important technology to ensure the security of sensitive information. Different image encryption schemes are outlined in this paper, such as optical transformation [1][2][3][4], cellular automata [5][6][7], DNA coding [8][9][10][11][12], data encryption standard (DES) [13][14][15], advanced encryption standard (AES) [16][17][18][19][20], and Blowfish [21]. However, the last three were mainly designed for textual information rather than digital image information.…”
Section: Introductionmentioning
confidence: 99%